Determining the contributing factors towards consumer online purchase intention amongst university students / Che Nur Asmani Amirah Che Mohd Nawi … [et al.] - Che Mohd Nawi, Che Nur Asmani Amirah; Ismail, Nur Liyana; Mohd Rashidi, Nur Zur’Aini; Nik Aziz, Nik Nor Faqihah (Unit Penerbitan, UiTM Kelantan, 2022)
Online shopping has emerged over the years from conventional one-to-one to electronic market (e-market space) as an integral part of users’ lives as a prominent alternative for conventional purchase. However, there is still limited research addressing online purchase intention from the perception of university students. Thus, this study aims to examine the factors that influence consumer online purchase intention among university students. Using convenient sampling techniques, 130 university students from University Teknologi MARA in Kelantan, Malaysia participated in this quantitative study. Consent was obtained from respondents before participating in the survey. The finding revealed that brand orientation, habitual behaviour, and quality orientation significantly influence consumer online purchase intention. However, this study imposed several limitations, such as a small number of respondents and a lack of other potential constructs.